Blood and Sand : Suez, Hungary and the Crisis that Shook the World - Tunzelmann, Alex Von (UK Simon & Schuster, 2016)
The thrilling account of sixteen extraordinary days in October and November 1956, when the twin crises of Suez and Hungary pushed the world to the brink of a nuclear conflict.
Keywords: History -- Egypt Suez -- Hungary